ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI MINAT MASYARAKAT DALAM MENGGUNAKAN LAYANAN E-BANKING PT BANK RAKYAT INDONESIA, Tbk - Ignasius Narew; Irmawati Irmawati (Unit Pengelola dan Pengembangan Jurnal Ilmiah dan Informasi (UPPJII) STIE Jambatan Bulan, 2022)
This study aims to determine: The effect of knowledge, trust and usefulness on interest in using E-banking PT Bank Rakyat Indonesia, Tbk. This research includes associative research with a sample of 100 respondents. Analysis of the data used to test the hypothesis is to use multiple linear regression analysis techniques. The results showed that (1) Knowledge had a positive and significant effect on interest in using E-banking. (2) Trust has a positive and significant effect on interest in using E-banking. (3) The usefulness has a positive and significant effect on the interest in using E-banking. (4) Knowledge, Trust and Benefit together have a positive and significant effect on interest in using E-banking PT Bank Rakyat Indonesia, Tbk